The role of the employees' individual resources in the perception of the work overload. Issue 3 (2nd March 2021) - Pluta, Anna; Rudawska, Aleksandra
Abstract : Purpose: The contemporary world's pressure, oriented on flexibility and quick actions, has permanently changed work characteristics. Taking the employees' perspective into account, it seems important to identify whether and which of the employees' individual resources help them cope with those job demands. Therefore, the main research question is what is the relation between holistically conceptualised employees' individual resources and perceived work overload? Design/methodology/approach: Based on the literature on individual resources and job demands, the authors test for relations between three components of individual resources (physical, emotional, spiritual potentials) and job characteristics (work variability and work diversity) and the perceived work overload. Data were collected using a survey method amongst 336 Polish knowledge workers. Findings: The results partially supported the posed hypotheses. Both work variability and work diversity relate positively to work overload. Only the physical potential is related directly and negatively to perceived work overload. The spiritual potential relates indirectly to work overload through work diversity. The authors also found that age moderates the relation between physical and spiritual potential and overload. Research limitations/implications: Human resource management (HRM) practitioners and supervisors need to consider the level of employee's individual resources, especially when dealing with older employees and their physical resources. Originality/value: This study contributes to research on the causes of work overload perception by identifying the role of individual resources and employees' age, thereby indicating that taking care of those resources could be another way of preventing occupational burnout in demanding work conditions.